2021
DOI: 10.1155/2021/4431416
|View full text |Cite
|
Sign up to set email alerts
|

UserRBPM: User Retweet Behavior Prediction with Graph Representation Learning

Abstract: Social and information networks such as Facebook, Twitter, and Weibo have become the main social platforms for the public to share and exchange information, where we can easily access friends’ activities and in turn be influenced by them. Consequently, the analysis and modeling of user retweet behavior prediction have an important application value, such as information dissemination, public opinion monitoring, and product recommendation. Most of the existing solutions for user retweeting behavior prediction ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…The method saved the required resources by utilizing high-performance parallel computing of Graphics Processing Units (GPU) in cloud computing services. In Huihui et al (2021), a UserRBPM framework to predict the action status of a user given the action statuses of her near neighbours and her local structural information was proposed. Experiments on a large-scale real-world dataset have shown that the User RBPM significantly outperformed baselines with handcrafted features in user retweet behaviour prediction.…”
Section: Sentiment Analysismentioning
confidence: 99%
“…The method saved the required resources by utilizing high-performance parallel computing of Graphics Processing Units (GPU) in cloud computing services. In Huihui et al (2021), a UserRBPM framework to predict the action status of a user given the action statuses of her near neighbours and her local structural information was proposed. Experiments on a large-scale real-world dataset have shown that the User RBPM significantly outperformed baselines with handcrafted features in user retweet behaviour prediction.…”
Section: Sentiment Analysismentioning
confidence: 99%